Credit constraints and the extensive margins of exports: First evidence for German manufacturing - Joachim Wagner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2015)
This paper uses a unique newly constructed data set to investigate for the first time the link between credit constraints and the extensive margins of exports in Germany, one of the leading actors on the international market for goods. In line with theoretical considerations and comparable results reported for a small number of other countries we report a negative impact of credit constraints on both the number of goods exported and the number of export destination countries that is both statistically highly significant and large from an economic point of view.
Keywords: F14; 330; credit constraints; exports; extensive margins